A tri-national initiative to advance understanding of coastal and ocean acidification in the Gulf of Mexico/Gulf of America - Hall, Emily R.; Hu, Xinping; Vreeland-Dawson, Jennifer; Yates, Kimberly K.; Besonen, Mark; Brenner, Jorge; Barbero, Leticia; Herzka, Sharon Z.; Hernández-Ayon, Jose Martín; Simoes, Nuno; González-Díaz, Patricia (Frontiers in Marine Science, 2025)
The Gulf of Mexico’s (also recognized by the United States government as the Gulf of America; herein referred to as “the Gulf”) valuable and diverse marine, coastal, and estuarine environments sustain many habitats, species, and economically important fisheries that are vulnerable to open ocean and coastal acidification (OOCA), including shellfish, coral reefs, and other carbonate reefs and seafloor. OOCA poses an economic threat to the Gulf’s economy, which is estimated to have a combined value of 2.04 trillion (US) per year across Cuba, Mexico and the United States (U.S.). Scientists from Cuba, Mexico, and the U.S. co-organized and co-hosted the first Gulf International Ocean Acidification Summit on Oct. 18-19, 2022 in Mérida, Yucatan, Mexico to exchange information and begin development of a new tri-national network to address the socioeconomic and ecological impacts of OOCA in the Gulf based on common needs. The meeting included representatives from government agencies, universities, research institutes, non-governmental organizations, and was sponsored by the Furgason Fellowship of the Harte Research Institute at Texas A&M University-Corpus Christi. Discussions focused on each country’s challenges, including known and potential socioeconomic vulnerabilities and biological and ecosystem responses to OOCA. Shared priorities were identified for observational, biological, environmental needs, socioeconomic research, outreach, and communications. Priority geographic locations for the study and short and long-term monitoring of OOCA were identified based on the group’s knowledge of oceanographic conditions and vulnerable regions. Longer-term actions that will help support multinational collaborations include: identifying shared data and information platforms; standardizing chemical and biological sampling methodologies; coordinating communications with regulatory agencies and resource managers; and coordinating monitoring activities, collaborative research projects, and tri-national comparisons and synthesis of findings. We present guidance from this effort for an integrated, multinational approach to understanding the causes and consequences of OOCA in the Gulf.